Reactivation of Aggressive Retinopathy of Prematurity Following Intravitreal Bevacizumab: Doi: 10.36351/pjo.v41i1.1924 - Wetarini, Krisnhaliani; Sutyawan, I Wayan Eka; Surasmiati, Ni Made Ayu; Andayani, Ari; Suryathi, Ni Made Ari (Pakistan Journal of Ophthalmology, 2025)
Aggressive Retinopathy of Prematurity (A-ROP) is a severe and rapidly progressing form of ROP that can lead to blindness if not managed effectively. Intravitreal Bevacizumab injection has emerged as a primary treatment option for A-ROP; however, the risk of recurrence necessitates vigilant follow-up and management. We present a case of 5-week-old premature male infant, diagnosed with bilateral A-ROP during routine screening and received an intravitreal Bevacizumab injection. Initial treatment resulted in clinical improvement, but one month later, the patient developed fibrosis, traction, and retinal neovascularization in the right eye, while the left eye showed signs of regression. Laser photocoagulation therapy was subsequently administered to manage the disease progression. This case report underscores the complexities in managing A-ROP, particularly the potential for reactivation following Bevacizumab treatment. A combined therapeutic approach, including laser photocoagulation, may be necessary to achieve optimal control of A-ROP progression.